PRODUCT DIFFERENTIATION AND MARKETING STRATEGIES OF ALPHONSO MANGO: A LITERATURE REVIEW WITH REFERENCE TO PUNE REGION - Jadhav, Vinay Nivrutti; Walke, Shrikrishna Gulabrao (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Alphonso mango, often referred to as the "King of Mangoes," holds a distinctive place in India’s horticultural landscape due to its superior taste, aroma, and texture. The Pune region, known for its proximity to key Alphonso-producing districts like Ratnagiri and Devgad, plays a pivotal role in its domestic marketing and distribution. This literature review investigates the product differentiation and marketing strategies applied to Alphonso mangoes with a focus on the Pune region. Product differentiation has been examined in terms of geographical indication (GI) tagging, organic certification, packaging innovations, and traceability systems. These differentiators help in distinguishing Alphonso from other mango varieties in the highly competitive fruit market. The review also analyzes marketing strategies including direct-to-consumer models, online marketplaces, traditional mandi systems, and export-oriented practices. Several studies reveal the increasing role of branding, quality assurance, and digital marketing in creating consumer trust and loyalty. Farmer producer organizations (FPOs), cooperatives, and government interventions have further strengthened the supply chain and market reach. However, challenges persist due to price volatility, counterfeit labeling, and lack of cold-chain infrastructure. The literature suggests that integrating sustainable farming practices with modern marketing tools can enhance the competitiveness of Alphonso mangoes. The review highlights gaps in localized consumer behavior studies and calls for further empirical research in the Pune region to devise region-specific strategies. The findings emphasize the need for a synergistic approach combining product excellence with market innovation for sustainable growth in Alphonso mango commerce.